2023
DOI: 10.1073/pnas.2305414120
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised embedding of trajectories captures the latent structure of scientific migration

Dakota Murray,
Jisung Yoon,
Sadamori Kojaku
et al.

Abstract: Human migration and mobility drives major societal phenomena including epidemics, economies, innovation, and the diffusion of ideas. Although human mobility and migration have been heavily constrained by geographic distance throughout the history, advances, and globalization are making other factors such as language and culture increasingly more important. Advances in neural embedding models, originally designed for natural language, provide an opportunity to tame this complexity and open new avenues for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Figure 2 c–d plots some examples of author mobility in the embedding space—as a researcher's career progresses, her publishing venue moves between different periodicals (i.e., journals and proceedings), forming a unique publication trajectory in the space of scientific periodicals. Prior studies have demonstrated that the embedding models can learn a systematic representation of mobility in the cases of institution locations 16 and research topics 15 . Hence, we expect the reconstructed trajectories from the embeddings of scientific periodicals to provide meaningful information about individual scientific activities and career profiles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 c–d plots some examples of author mobility in the embedding space—as a researcher's career progresses, her publishing venue moves between different periodicals (i.e., journals and proceedings), forming a unique publication trajectory in the space of scientific periodicals. Prior studies have demonstrated that the embedding models can learn a systematic representation of mobility in the cases of institution locations 16 and research topics 15 . Hence, we expect the reconstructed trajectories from the embeddings of scientific periodicals to provide meaningful information about individual scientific activities and career profiles.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the complexity of trajectory data, we use single quantitative measures. Here, we introduce four measures, including the mean embedding distance 16 , the average distance to the midpoint, the radius of gyration in the original space, and the radius of gyration in the 2-d space 23 . In particular, the radius of gyration, , is a well-known indicator in mobility analysis that measures the characteristic distance traveled by an individual 27 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations